Stakeholders’ perspectives on barriers to and facilitators of school-based HPV vaccination in the context of COVID-19 pandemic-related disruption: a qualitative mixed methods study - Amal Khan; Sylvia Abonyi; Cory Neudorf; Sandro Galea; Shahid Ahmed (International Journal of Qualitative Studies on Health & Well-Being, 2024)
Despite successfully implementing the Human Papilloma Virus Vaccine (HPVV) program, Saskatchewan (SK) struggled to improve HPVV uptake rates. This suboptimal uptake of HPVV with a status quo of HPV-linked cervical cancer incidence rate is mainly because HPVV’s impact on cancer prevention has not been realized adequately by vaccine providers and receivers. Further exploration of determinants of HPVV uptake is required to uncover high-resolution quality improvement targets for investment and situate contextually appropriate policies to improve its uptake. The study undertook a qualitative inquiry into understanding stakeholders’ perspectives on HPVV experience through school-based programmes. It collected data through semi-structured initial interviews (N = 16) and follow-up interviews (N = 10) from across Saskatchewan’s four Integrated Service Areas. Document analysis was conducted on all publicly available documents that included information on HPVV from January 2015 to July 2023. Thematic analysis of the data identified that inadequate information, awareness and education about HPV infection and HPVV among several groups, especially, parents, youth and school staff, was the main barrier to optimal HPVV uptake. Vaccine-related logistics, including the technical and text-heavy vaccine information sheet, understaffing, and time constraints, were other important factors that impeded HPVV uptake. A person-centred approach could educate parents in multiple dimensions.